Quasi Experimental Study to Assess the Effect of Planned Teaching Programme on the Knowledge Regarding Modifiable Risk Factors of Coronary Artery Disease among Adolescents in Selected Junior Colleges - Patkar, Suvarnarekha; Gholap, Gayatri (Indian Journal of Nursing Sciences, 2024)
Introduction: Stress and anxiety have adverse effects on the body system. One of which is on circulatory system, that is, the blood vessels and the blood but the individual continues to remain asymptomatic due to the gradual onset and progressive damage occurring to the blood vessels, coronary artery disease (CAD) (arthrosclerosis). According to the WHO, in 2013 CAD was most common cause of death globally, resulting in 8.14 million deaths (16.8%) up from 5.74 million deaths (12%) in 1990. In the United States in 2010 about 20% of those over 65 had CAD, while it was present in 7% of those 45–64, and 13% of those 18–45. Rates are higher among women then male of given age. This study shows that cardiovascular risk factor is highly prevalent among school children, importantly; school children lack adequate knowledge regarding cardiovascular risk factors. School based intervention is required for cardiovascular risk reduction in childhood. Aim: The aim of the study was to assess the effect of planned teaching programme (PTP) on knowledge regarding modifiable risk factors of CAD among adolescents in selected junior college. Subject and Method: One group pre- and post-test research design was adopted. Astructured teaching program and questionnaire administered to asses pre- and post-test knowledge regarding risk factors of CAD among adolescents. Results: We observed that knowledge measured after PTP was significantly better (P < 0.05). There were no associations of knowledge with any demographic variables. Conclusion: Planned teaching was effective measured to improve knowledge regarding modifiable risk factors of CAD among adolescents in selected junior college.